An Investigator's Discretion in State Assets Confiscation Criminal Action Case of Corruption - Adi Wiratmoko; Amin Purnawan; Siti Ummu Adillah (Law Development Journal, 2022)
This research aims to discuss the concept of investigators' discretionary power in applying their powers and authorities in confiscation of state assets and shifting the terms of discretion from Act No. 14 of 2014 concerning Government Administration to Act No. 11 of 2022 concerning Job Creation. This discussion aims to provide clarity on the concept of discretionary power of investigators in confiscation of state assets which is still controversial from various aspects so that the concept of discretionary power is not only acceptable in terms of power, but also legally and morally/ethically acceptable. This writing uses a doctrinal (juridical-normative) approach, namely research on criminal law norms contained in Indonesian criminal legislation. Based on the results of the study, it was concluded that in principle the application of the investigator's discretionary power to confiscate state assets in corruption cases is a must because the spirit of eradicating corruption is to restore lost state assets. This discretionary power must also be balanced with improving the quality and integrity of investigators, in particular.